2021
DOI: 10.4269/ajtmh.20-0088
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations Associated with Bartonella henselae Infection in a Tropical Region

Abstract: Bartonella henselae is a zoonotic Gram-negative Bacillus associated with self-limited regional lymphadenopathy. In recent decades, an expanding spectrum of clinical manifestations has been described, in part, due to improved diagnostics. However, updated epidemiological data are sparse. We retrospectively reviewed the clinical features of 31 patients with B. henselae infection over 15 years from 2005 to 2019, in the tropical Top End of Australia. Our annual disease incidence of 1.3 cases per 100,000 population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
3
0
1
Order By: Relevance
“…Bartonella henselae (n=7) causes cat scratch disease (CSD). In most cases, in the neck region in the adult individual, it manifests itself with serous inflamed lymph nodes, and rarely, it reaches the stage of purulent involvement [16]. More often, the formation of purulent exudate in the cervical lymph nodes is reached in children [17].…”
Section: Discussionmentioning
confidence: 99%
“…Bartonella henselae (n=7) causes cat scratch disease (CSD). In most cases, in the neck region in the adult individual, it manifests itself with serous inflamed lymph nodes, and rarely, it reaches the stage of purulent involvement [16]. More often, the formation of purulent exudate in the cervical lymph nodes is reached in children [17].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the occurrence of an embolic stroke caused by B. henselae is considered rare. Following a comprehensive review of the literature, it appears that only a small number of articles have reported on the correlation between cerebral vascular accidents and Bartonella IE [20][21][22][23][24]. However, that association should not be overlooked.…”
Section: Cerebral Embolic Events Associated With B Henselae Iementioning
confidence: 99%
“…Bartonellosis refers to a group of infectious diseases caused by Bartonella, a gram-negative coccobacillus with tropism for endothelial cells. Bartonella henselae , quintana and bacilliformis are responsible for the majority of human diseases 1 2. The most common symptoms of B. henselae and B. quintana present 7 to 10 days after inoculation and include cutaneous rash, localised lymphadenopathy, fever and malaise 1.…”
Section: Introductionmentioning
confidence: 99%